The road to academic excellence : the making of world-class research universities - Salmi, Jamil; Altbach, Philip G. (Washington DC : World Bank, 2011)
The book examines the experience of 11 universities in 9 countries that have grappled with the challenges of building successful research institutions in difficult circumstances and presenting the lessons learnt from these experiences.
Includes bibliographical references and index.
oif 18/07/2018
Loans
Keywords: Education, Higher; Economic development; Universities and colleges; Higher education and state; Education and globalization